Information System on Marine Ecology - kannan, L.; Kannan, R. (DESIDOC Journal of Library & Information Technology, 2003)
Increasing exploitation of marine resources coupled with increasing level of pollutants and endless pressure of human population is posing a threat to marine habitat.united Nations has also emphasised on the protection and sustainable development of marine and coastal areas of the national,sub-regional and global levels.In this situation,Information Systems are assuming an ever increasing importance in the development .the authors describe the sources and services provided by the ENVIS Centre at the Centre of advanced Study in Marine Biology. http://dx.doi.org/10.14429/dbit.19.2.3478